Return to active duty after anterior cruciate ligament reconstruction (ACLR) in Chinese male military aircrews - Zhang, Hongxing; Yang, Fengyuan; Xie, Bowen; Chen, Zhiqiang; Peng, Ye; Chen, Yufei; Li, Tianqi; Huang, Xiaogang; Xue, Jing; Du, Junjie (Frontiers in Surgery, 2023)
Background: Surgically treated anterior cruciate ligament (ACL) injuries may be a waivable condition and allow return to full flight status, but waivers are based on expert opinion rather than recent published data. The purpose of this study was to evaluate return to flight after anterior cruciate ligament reconstruction (ACLR) in male military aircrews with ACL injuries and to identify factors that affect flight clearance. Method: A single-center retrospective review was conducted by the authors for all active-duty aircrew who underwent ACLR at an authorized military medical center from January 2010 to December 2019. Demographic characteristics, occupational information, surgical data, and flight readiness evaluation outcomes were collected. Based on the final medical evaluation, subjects were divided into a qualified group (N = 64) and a disqualified group (N = 9), and the difference in data collected between the two groups was then analyzed to identify factors affecting flight clearance. Results: A total of 73 patients underwent successful ACLR with a mean age of 31.6 ± 5.6 years. Non-contact injury was the main type of ACL injury, accounting for 84.9% of the total injuries. 55 cases (75.3%) occurred during daily sports activities and 18 (24.7%) during military training. 64 of the 73 crewmembers (87.7%) were able to return to flight at their last follow-up evaluation. The preoperative interval time (PIT) was significantly less in the qualified group than in the disqualified group (P = 0.002). Patients who underwent ACLR within three months were more likely to return to flying than those who underwent the procedure three months later (97.4% vs. 76.5%, P = 0.010). The incidence of failure to return to flight duty was significantly higher in aircrews with ACL injuries combined with meniscal injuries than in aircrews with isolated ACL injuries (21.4% vs. 0.0%, P = 0.017). Conclusion: ACLR appears to be safe for military aircrew suffering ACL injuries with or without meniscal injury, and return to flight status is the most likely outcome for the majority of postoperative pilots. Prolonged PIT, PIT > 3 months, and ACL injury combined with meniscus injury had a negative impact on postoperative flight readiness.